Modeling and Estimation of Synchronization in Multistate Markov-Switching Models - Cem Cakmakli; Richard Paap; Dick J.C. van Dijk (Tinbergen Institute, 2011)
This paper develops a Markov-Switching vector autoregressive model that allows for imperfect synchronization of cyclical regimes in multiple variables, due to phase shifts of a single common cycle. The model has three key features: (i) the amount of phase shift can be different across regimes (as well as across variables), (ii) it allows the cycle to consist of any number of regimes J is larger than or equal to 2, and (iii) it allows for regime-dependent volatilities and correlations. In an empirical application to monthly returns on size-based stock portfolios, a three-regime model with asymmetric phase shifts and regime-dependent heteroscedasticity is found to characterize the joint distribution of returns most adequately. While large- and small-cap portfolios switch contemporaneously into boom and crash regimes, the large-cap portfolio leads the small-cap portfolio for switches to a moderate regime by a month.
Keywords: C11; C32; C51; C52; 330; imperfect synchronization; phase shifts; regime-switching models; Bayesian analysis; Zeitreihenanalyse; Markovscher Prozess; Theorie